SAT0429 Circulating Levels of IC3B and C3 Levels Correlate with Sledai-2K Responder Index-50 (S2K RI-50) Disease Activity Scores – the Castle (Complement Activation Signatures in Systemic Lupus Erythematosus) Study. (9th June 2015) - Kim, A.H.; Strand, V.; Mathis, N.; Fairweather, W.R.; Sen, D.P.; Sinclair, K.C.; Miner, J.J.; Schramm, E.C.; Bruchas, R.R.; Staten, N.; Olson, P.; Stiening, C.M.; et al.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a heterogeneous autoimmune disease characterized by autoantibody production and complement activation, leading to protean manifestations with significant morbidity and mortality. A major unmet need in SLE is a biomarker that tracks with disease activity. One current approach is measuring complement activation by evaluating consumption of serum C3 and C4 components. As they are also acute phase reactants, production of C3 and C4 can balance consumption and serum levels may not decrease until late in a flare. iC3b is an inactive proteolytically derived molecule of C3b, with a short serum half-life (t1/2 =30-90 minutes) (1). Increases in iC3b levels correlate with complement activation and the iC3b/C3 ratio is elevated when consumption exceeds production (2). Objectives: To correlate iC3b and C3 levels and elevated iC3b/C3 ratios with disease activity measured by S2K RI-50, anti-dsDNA Abs by ELISA, ESR and CRP. Methods: 82 adult SLE patients (89.0% female, age (mean ± SD): 41.4±12.9, S2K RI-50 score: 5.32±6.14) were enrolled from the Washington University Lupus Clinic. C3 was measured by nephelometry, and blood iC3b was assessed using the Kypha COMP ACT ™ test, a lateral flow point of care assay. Analyses were restricted to the initial visit. Linear models analysis was used to generate predictive models of S2K RI-50 scores based on iC3b, C3, ESR, dsDNA, CRP levels and prednisone dose (≤7.5 mg/day versus >7.5 mg/day). Results: Blood iC3b (P<0.001, R 2 =0.1549; Figure 1A ), C3 (P<0.001, R 2 =0.2011; Figure 1B ), dsDNA (P<0.0003, R 2 =0.153), and ESR (P<0.038, R 2 =0.058) each correlated with concurrent S2K RI-50 scores, while CRP (P<0.26, R 2 =0.017) did not. C3 correlated inversely; the others positively. The ratio of iC3b/C3 (P<0.001, R 2 =0.2447) more strongly correlated with S2K RI-50 scores than any other individual parameter (Figure 1C ). Linear models analysis yielded two separate models: in model 1, iC3b, C3, prednisone dose, and ESR were jointly predictive of S2K RI-50 scores (P<0.001, R 2 =0.4359). In model 2, iC3b, iC3b/C3 ratio, and prednisone dose were jointly predictive (P<0.001, R 2 =0.3846). In both models, dsDNA and CRP did not contribute to the predictive value. Conclusions: Blood iC3b levels correlated with S2K RI-50 scores, further strengthened when the iC3b/C3 ratio was used – this may represent a new biomarker of SLE disease activity. Both linear models confirmed the predictive value of iC3b as well as C3 to S2K RI-50 scores. While limitations exist when utilizing single visit data, these data warrant further investigation of iC3b as a promising approach to assessing disease activity in SLE. References: Ross et al., J. Immunol., 129:2051, 1982 Lambris. Immunol. Today, 9:387, 1988 Disclosure of Interest: A. Kim Grant/research support from: Kypha, Inc., Consultant for: Pfizer, Amgen, Janssen, V. Strand Consultant for: Abbvie, Amgen Corporation, Anthera, AstraZeneca, BMS, Genentech/Roche, GlaxoSmithKline, Janssen, Lilly, MerckSerono, Novartis, Pfizer, Takeda, UCB, N. Mathis Consultant for: Kypha, Inc., W. Fairweather: None declared, D. Sen: None declared, K. Sinclair: None declared, J. Miner: None declared, E. Schramm Consultant for: Kypha, Inc., R. Bruchas Employee of: Kypha, Inc., N. Staten Employee of: Kypha, Inc., P. Olson Employee of: Kypha, Inc., C. Stiening Employee of: Kypha, Inc., J. Atkinson: None declared